PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS POWTOON DENGAN PENDEKATAN FLIPPED CLASSROOM PADA MATERI SUHU DAN KALOR KELAS XI SMA - Laura Yasa; Zulhelmi Zulhelmi; M. Nor M. Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Student motivation is still low, time is limited in learning physics, and there are some abstract learning materials that are difficult to understand, resulting in misconceptions. So a research was carried out on the development of powtoon-based learning videos with the flipped classroom approach on temperature and heat material for class XI SMA which aims to develop and determine the validity of powtoon-based learning videos along with learning tools in the form of RRP and LKPD so that they can be an alternative in solving some of these problems. This study uses the Research and Development method with the ADDIE development model which in practice is carried out only up to the development stage. From the average results of the video validation, RPP, and LKPD, it is found that the categories are very valid, valid, and valid, so that they are declared worthy of being used in learning.Key Words: Learning Videos, Powtoon, Flipped Classroom, Temperature and Heat